Unveiling Consumer Preferences: Exploring Factors Influencing Purchase Decisions in the Jewellery Market - Soni, Parth; Chauhan, Rahul; Patel, Mohit; Patel, Himalay; Kalariya, Kush (Indonesian Journal Publisher, 2024)
This study investigates consumer-buying behavior in the traditional and branded jewellery market, focusing on factors influencing purchase decisions and overall satisfaction. Data from 240 respondents in Gujarat, India, were analyzed using factor analysis and Smart PLS. Results indicate a preference for traditional jewellery, with brand image and personal style significantly affecting overall satisfaction. Conversely, factors related to price and traditional values may not have a significant relationship with satisfaction. Future research could explore cultural influences on consumer preferences and conduct comparative studies across different regions. Understanding consumer behavior in the jewellery market has implications for businesses globally, enabling them to tailor marketing strategies and product offerings to meet customer needs effectively.